2014
DOI: 10.1371/journal.pone.0089134
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Transcriptome-Derived Microsatellite Markers and Their Association with the Growth Performance of the Mud Crab (Scylla paramamosain)

Abstract: Microsatellite markers from a transcriptome sequence library were initially isolated, and their genetic variation was characterized in a wild population of the mud crab (Scylla paramamosain). We then tested the association between these microsatellite markers and the growth performance of S. paramamosain. A total of 129 polymorphic microsatellite markers were identified, with an observed heterozygosity ranging from 0.19 to 1.00 per locus, an expected heterozygosity ranging from 0.23 to 0.96 per locus, and a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 31 publications
3
23
1
1
Order By: Relevance
“…In the present study, a total of five type I microsatellite loci were found to be polymorphic using a G 1 family. The genetic diversity (mean H O = 0.50) was much lower than that of type II loci (mean H O = 0.76; Ma et al, 2010), and even lower than that of type I loci developed in a previous study (mean H O = 0.68; Ma et al, 2014a). Aside from the major reason of microsatellite loci themselves, this difference may be due to the types and sizes of populations (wild, cultured, or a single family) used.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…In the present study, a total of five type I microsatellite loci were found to be polymorphic using a G 1 family. The genetic diversity (mean H O = 0.50) was much lower than that of type II loci (mean H O = 0.76; Ma et al, 2010), and even lower than that of type I loci developed in a previous study (mean H O = 0.68; Ma et al, 2014a). Aside from the major reason of microsatellite loci themselves, this difference may be due to the types and sizes of populations (wild, cultured, or a single family) used.…”
Section: Discussioncontrasting
confidence: 63%
“…In order to acquire as many markers as possible, we first developed polymorphic microsatellite markers from the transcriptome, using a previously described method (Ma et al, 2014a). Then, we collected all published microsatellite markers for S. paramamosain (Xu et al, 2009;Ma et al, 2011a,b,c;Cui et al, 2011b;Yao et al, 2012;Song et al, 2013;Ma et al, 2014a,b).…”
Section: Microsatellite Markers and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Next‐generation sequencing has recently been used to identify transcriptome‐derived microsatellites (SSRs) and polymorphic nucleotide positions such as SNPs, and it is considered a time‐saving, highly efficient approach (Li et al ; Ma et al . ; Wang et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Isolation and utilization of microsatellite markers has been carried out in many species (Wang et al 2009;Ma et al 2011Ma et al , 2014. Currently, no polymorphic microsatellite markers have been reported for S. aurita.…”
Section: Introductionmentioning
confidence: 99%